Every day : the graphic novel - Levithan, David (Alfred A. Knopf, 2023)
Every morning A wakes in a different person's body, in a different person's life, learning over the years to never get too attached, until he wakes up in the body of Justin and falls in love with Justin's girlfriend, Rhiannon.